Apresentação do tráfego de dados de um barramento CAN em uma interface gráfica desenvolvida em Java - Pinto, Eduardo Felipe Cordeiro (2018)
Due to the low number of references about the connection between graphic interfaces and PIC microcontrollers, connected to a CAN bus, it was decided to develop a document which exposes the main developed features at this project. For this, it was realized a bibliographic revision with relation to the data communication models used, as well as a brief introduction to the programming languages. As a result of this research, has developed a graphic interface, allowing the data sending and receiving to the CAN bus. The used codes are shown by flowcharts and algorithms.